2011
DOI: 10.1016/j.jvs.2010.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative C-arm cone-beam computed tomography in fenestrated/branched aortic endografting

Abstract: CBCT is a valuable addition to complicated aortic interventions such as FEVAR. Intraoperative use utilizing fusion imaging limits contrast dosage and postdeployment CBCT is of sufficient quality to evaluate successful aneurysm exclusion and for detection of early complications after FEVAR. With the information we are able to obtain from the CBCT at the completion of the FEVAR, we can intervene on problems earlier and potentially decrease the subsequent need for reintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
114
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(121 citation statements)
references
References 14 publications
6
114
1
Order By: Relevance
“…Tacher et al 18 have also described, in a small series of patients undergoing endovascular thoracoabdominal aortic aneurysm repair with image fusion, a significant decrease in contrast injection. Those results are consistent with the previous report from Dijkstra et al 5 In accordance with Dijkstra et al, 5 we did not observe a significant reduction in total operative time when using fusion.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Tacher et al 18 have also described, in a small series of patients undergoing endovascular thoracoabdominal aortic aneurysm repair with image fusion, a significant decrease in contrast injection. Those results are consistent with the previous report from Dijkstra et al 5 In accordance with Dijkstra et al, 5 we did not observe a significant reduction in total operative time when using fusion.…”
Section: Discussionsupporting
confidence: 94%
“…18 A significant reduction in contrast medium volume injected was reported (from 235 AE 145 mL to 65 AE 28 mL), but no differences in DAP values nor in procedure time were seen. Dijkstra et al 5 reported the first cohort of 40 patients treated with fenestrated or branched endografts under intraoperative guidance. A CBCT was performed to overlay the preoperative CTA by 3D/3D registration on bony landmarks.…”
Section: Discussionmentioning
confidence: 99%
“…This is, however, not the first time that image fusion technology has been evaluated in the setting of endovascular surgery. Dijkstra et al 7 They compared three different imaging techniques: 2D angiography, 3D angiography, and image fusion technology similar to VesselNavigator. They showed a trend toward reduction of radiation dose for the fusion group (1188 6 1067 Gy $ cm 2 and 984 6 581 Gy $ cm 2 for 2D angiography and 3D angiography, respectively, vs 656 6 457 Gy $ cm 2 for the fusion group; P ¼ .18).…”
Section: Discussionmentioning
confidence: 99%
“…Intra-operative guidance during EVAR is usually performed with X-ray fluoroscopy. Both intraoperative CT (Dijkstra et al, 2011) as well as fluoroscopy in combination with navigation using electromagnetic sensors (Manstad-Hulaas et al, 2007) has been investigated for guiding insertion of fenestrated grafts. Some investigators have also reported transabdominal ultrasound for guidance of EVAR.…”
Section: Ultrasound In Endovascular Treatmentmentioning
confidence: 99%